Conventional Criticism of an Unconventional Text: on Samuel Beckett's Ping Conventional Criticism of an Unconventional Text: on Samuel Beckett's Ping - Maria Helena Peixoto Kopschitz (Ilha do Desterro, 2008)
Robert Scholes once affirmed that the sense of design is
essential to a full reading experience and that in fiction it takes
many forms, which are mainly of two kinds: juxtaposition and
repetition. I If so one of the very causes of difficulty in "Ping",
its repetitive nature and its elusive permutations, can turn into
guidelines for its analysis.
Beckett's rhetoric of repetition operates as a cumulative
process, which allows us to distinguish the fundamental semantic constituents of "Ping". Hence it is possible to try to organize items that correspond to the traditional elements of fiction, as stated below. In order to make the work less hard for the eyes and the mind, I have recopied the seventy sentences of "Ping", each one separately, and numbered them. I shall refer to the numbers in my text. (See Appendix.) Robert Scholes once affirmed that the sense of design is
essential to a full reading experience and that in fiction it takes
many forms, which are mainly of two kinds: juxtaposition and
repetition. I If so one of the very causes of difficulty in "Ping",
its repetitive nature and its elusive permutations, can turn into
guidelines for its analysis.
Beckett's rhetoric of repetition operates as a cumulative
process, which allows us to distinguish the fundamental semantic constituents of "Ping". Hence it is possible to try to organize items that correspond to the traditional elements of fiction, as stated below. In order to make the work less hard for the eyes and the mind, I have recopied the seventy sentences of "Ping", each one separately, and numbered them. I shall refer to the numbers in my text. (See Appendix.)